IDNLearn.com offers a comprehensive solution for finding accurate answers quickly. Our community provides timely and precise responses to help you understand and solve any issue you face.
Sagot :
Let us analyze and correct the given steps in solving the equation:
The original equation is:
[tex]\[ -2(7 - y) + 4 = -4 \][/tex]
Let's solve this equation step-by-step:
### Step 1: Distribute the -2
Multiply both terms inside the parentheses by -2:
[tex]\[ -2 \cdot 7 + (-2) \cdot (-y) + 4 = -4 \][/tex]
[tex]\[ -14 + 2y + 4 = -4 \][/tex]
### Step 2: Combine like terms
Combine the constant terms on the left side:
[tex]\[ -14 + 4 + 2y = -4 \][/tex]
[tex]\[ -10 + 2y = -4 \][/tex]
### Step 3: Isolate the term involving [tex]\( y \)[/tex]
Add 10 to both sides to isolate the [tex]\( y \)[/tex]-term:
[tex]\[ -10 + 2y + 10 = -4 + 10 \][/tex]
[tex]\[ 2y = 6 \][/tex]
### Step 4: Solve for [tex]\( y \)[/tex]
Divide both sides by 2:
[tex]\[ y = \frac{6}{2} \][/tex]
[tex]\[ y = 3 \][/tex]
### Conclusion:
The error in the provided process occurred during the transition from the equation [tex]\(-10 - 2y = -4\)[/tex] to [tex]\(-2y = 6\)[/tex]. The correct algebraic steps show that [tex]\( y \)[/tex] should equal 3, not -3.
Therefore, the correct value of [tex]\( y \)[/tex] is:
[tex]\[ y = 3 \][/tex]
The original equation is:
[tex]\[ -2(7 - y) + 4 = -4 \][/tex]
Let's solve this equation step-by-step:
### Step 1: Distribute the -2
Multiply both terms inside the parentheses by -2:
[tex]\[ -2 \cdot 7 + (-2) \cdot (-y) + 4 = -4 \][/tex]
[tex]\[ -14 + 2y + 4 = -4 \][/tex]
### Step 2: Combine like terms
Combine the constant terms on the left side:
[tex]\[ -14 + 4 + 2y = -4 \][/tex]
[tex]\[ -10 + 2y = -4 \][/tex]
### Step 3: Isolate the term involving [tex]\( y \)[/tex]
Add 10 to both sides to isolate the [tex]\( y \)[/tex]-term:
[tex]\[ -10 + 2y + 10 = -4 + 10 \][/tex]
[tex]\[ 2y = 6 \][/tex]
### Step 4: Solve for [tex]\( y \)[/tex]
Divide both sides by 2:
[tex]\[ y = \frac{6}{2} \][/tex]
[tex]\[ y = 3 \][/tex]
### Conclusion:
The error in the provided process occurred during the transition from the equation [tex]\(-10 - 2y = -4\)[/tex] to [tex]\(-2y = 6\)[/tex]. The correct algebraic steps show that [tex]\( y \)[/tex] should equal 3, not -3.
Therefore, the correct value of [tex]\( y \)[/tex] is:
[tex]\[ y = 3 \][/tex]
We appreciate every question and answer you provide. Keep engaging and finding the best solutions. This community is the perfect place to learn and grow together. IDNLearn.com is committed to providing accurate answers. Thanks for stopping by, and see you next time for more solutions.